A molybdenum disulfide/nickel ferrite-modified voltammetric sensing platform for ultra-sensitive determination of clenbuterol under the presence of an external magnetic field. Issue 16 (3rd April 2023) - Tien, Van Manh; Ong, Van Hoang; Pham, Tuyet Nhung; Quang Hoa, Nguyen; Nguyen, Thi Lan; Thang, Pham Duc; Khanh Vinh, Le; Trinh, Pham Thi Nhat; Thanh, Doan Thi Ngoc; Tung, Le Minh; Le, Anh-Tuan
Abstract : The electrochemical behavior and sensing performance of an electrode modified with NiFe2 O4 (NFO), MoS2, and MoS2 –NFO were thoroughly investigated using CV, EIS, DPV, and CA measurements, respectively. Abstract : The electrochemical behavior and sensing performance of an electrode modified with NiFe2 O4 (NFO), MoS2, and MoS2 –NFO were thoroughly investigated using CV, EIS, DPV, and CA measurements, respectively. MoS2 –NFO/SPE provided a higher sensing performance towards the detection of clenbuterol (CLB) than other proposed electrodes. After optimization of pH and accumulation time, the current response recorded at MoS2 –NFO/SPE linearly increased with an increase of CLB concentration in the range from 1 to 50 μM, corresponding to a LOD of 0.471 μM. In the presence of an external magnetic field, there were positive impacts not only on mass transfer, ionic/charge diffusion, and absorption capacity but also on the electrocatalytic ability for redox reactions of CLB. As a result, the linear range was widened to 0.5–50 μM and the LOD value was about 0.161 μM. Furthermore, stability, repeatability, and selectivity were assessed, emphasizing their high practical applicability.